THE APPLICATION OF GEOMETRIC PROPORTION AND COMPOSITION THEORY TO THE BNI 46 JAKARTA BUILDING BY SILABAN - Ratnasarira (Jurnal Riset Arsitektur, 2017)
Abstract- In terms of history, proportion, composition and geometry have been applied as design elements since long ago, way before the era of modern architecture. The existence of these three elements enables numerous variations and produces freedom of expression. Unfortunately, in current design processes, these visual principles are often overlooked. In fact, they play a role as one of the indicators of aesthetics of a building, as well as exerting influence on human perception in capturing and perceiving a given space. The purpose of this research is to study the application of proportion and composition principles to one of the creations of the Indonesian modern architect Frederich Silaban. The BNI 46 Building design by Silaban acts as the research object, displaying a façade which is crammed with modern thoughts, different on each side but remaining harmonious and visually attractive. The theory of proportion, composition, geometry and structuring principles provide the basis for analyzing the existing object. This research uses the descriptive analytical method with the qualitative approach to data collection of the research object. The next step is the vertical and horizontal analysis of the building enclosure in relation to the implementation of geometric proportion and composition principles in the building. This research is expected to be beneficial in terms of enriching the knowledge and study of geometric proportion and proportion in architecture, adding to the consideration of implementing visual principles for professionals, as well as adding to the archive/portfolio concerning Silaban as one of Indonesia’s pioneering modern architects. Keywords: proportion, composition, Geometry, Silaban